Spain : Financial Sector Assessment Program; Technical Note; Nonfinancial Equity Investments of Spanish Credit Institutions. (IMF Staff Country Reports; Country Report, 2006)
This note assesses the risk profile of the nonfinancial equity investments of Spanish credit institutions (CIs), based on a market-risk approach. It assesses the main features of the situation and indicates the problems of CIs' nonfinancial equity investments. It presents the evolution of nonfinancial equity investments, and their importance for the economy. It analyzes using the value-at-risk (VaR) approach and recommends enhancing of risk management practices and surveillance with regard to CIs with a significant nonfinancial equity investment, and encourages those CIs to adopt the market-based approach.